Electromobility in Poland and Slovakia. Benchmarking of Electric Vehicles for 2019 - Ewelina Sendek-Matysiak; Hubert Rzedowski; Tomas Skrucany (Communications - Scientific letters of the University of Zilina, 2020)
Since the entry into force of the Paris Agreement in 2015, and with the publication of the Intergovernmental Panel on Climate Change report on the consequences of 1.5 degrees of global warming, the issue of reducing greenhouse gas emissions in a cost-effective manner and within the timeframe outlined has become a matter of urgency. The transport sector, which accounts for a quarter of total GHG (Greenhouse Gas) emissions in the 28 EU Member States, is no exception. Due to the serious environmental impacts of transport, new mobility concepts are being implemented at both national and international levels. One of these is the large-scale deployment of electric vehicles, including those powered exclusively by Battery Electric Vehicle (BEV) batteries. They are quiet and virtually emission-free and, in terms of safety, have the feature that, in the event of an accident, they reduce the risk of detonating the vehicle and of burning or burning out the passengers. This article presents the current state of electromobility in Poland and Slovakia with an indication of light electric cars BEV and the most important factors stimulating its development.